Políticas públicas habitacionais para idosos : um estudo sobre os condomínios exclusivos - Monteiro, Luzia Cristina Antoniossi (2012)
Brazil is facing severe problems in relation to urban spaces theme. Some age groups such as the elderly have found more difficulties to ensure their socio-spatial integration. This issue, combined with the demand for proper housing and the exponential increase in the number of people aged over sixty years are causing a new challenge for Brazil in the XXI century: the responsibility to implement appropriate public policies for the inclusion of the elderly population in cities. Building the house" is not enough; we must effect new forms of housing that enable inclusion and social participation. The aim of this study was to analyze the typology of exclusive condominiums for elderly, among the modalities of public housing policies identified in the literature review and legislation. Four condominiums have been analyzed, performing visits in locus for interviewing managers and elderly residents. The condos selected for analysis have as a reference the housing program of the State of Sao Paulo called Vila Dignidade , which adopts the concept of "assisted housing" aiming to provide, besides the house, social assistance, protection, accessibility, comfort and safety. The cities of Avaré and Itapeva were the first to inaugurate the housing units included in the program. On the other hand the other two analyzed condominiums, Vila dos Idosos-Pari in Sao Paulo and Recanto Feliz in Araraquara, predate the state policies but have interesting features since they were built on idle properties, or free deconstructed spaces that has relieved onus to the urban space, already so transformed by anthropical action. The results suggest the need to diversify housing models, in view of suiting the heterogeneity of the elderly and the resident s profile in each location. To make the policies efficient is necessary that the state fulfills its role to achieve the social rights of citizens involving in this task, the society, the family and the elderly person.